Role of NADH Dehydrogenase (Ubiquinone) 1 alpha subcomplex 4-like 2 in clear cell renal cell carcinoma - Minton, Denise R.; Fu, Leiping; Mongan, Nigel P.; Shevchuk, Maria M.; Nanus, David M.; Gudas, Lorraine J. (American Association for Cancer Research, 2016)
PURPOSE